GSAEC - Acoustic echo cancellation embedded into the generalized sidelobe canceller - Herbordt, Wolfgang; Kellermann, Walter (Proc. European Signal Processing Conference (EUSIPCO), 2000)
In this paper, we examine the integration of acoustic echo cancellation (AEC) with a robust generalized side-lobe canceller (GSC) [2, 3] with regard to exploitable synergies. Since the AEC is located behind the fixed beamformer (FBF) of the GSC only one AEC is required for an arbitrary number of array elements. System analysis shows that ideal suppression of local interferers and of acoustic echoes cannot be achieved simultaneously. However, experiments confirm that the interference reduction (IR) is degraded by less than 3 dB compared to a cascade of AEC and GSC and that the echo reduction is improved by more than 13 dB relative to the GSC in echoic environments.